Indonesian State of Law is an Aspired Concept - Diya Ul Akmal (Nurani Hukum, 2021)
The state of law is the concept of a state based on applicable law. In the development of the state, there are two concepts of state of law used by countries in the world, namely rechtstaat and rule of law. These two concepts also inspired the Indonesian state of law but were not followed absolutely. Indonesia is still building a legal system with a culture of society. Therefore, this study aims to describe the development of the state of law in Indonesia. This study uses a normative juridical method by using secondary data and is narrated with scientific logic. Conceptually, Indonesia does not follow the concept of rechtstaat or the rule of law because it is different from national identity. The social condition of the community consisting of various ethnic groups forced Indonesia to develop its own concept of a state of law. There is hope in the formation of laws carried out by the state, which is not only to realize the rule of law but must provide benefits to the community. Pancasila as a crystallization of the values of people's lives can actually fulfill this goal, but until now it has not been realized properly. In law enforcement, community justice must be formulated as a mandatory thing to be implemented. Every individual in society must be protected every right he has. So that the concept of the state of law in Indonesia must be correlated with the formation of useful laws and fair law enforcement. If this has been formed and is running well, then the Indonesian state of law that is beneficial to the community is not just wishful thinking.